PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA ALOKASI UMUM (DAU) TERHADAP BELANJA MODAL KABUPATEN DAN KOTA DI PROVINSI KALIMANTAN BARAT TAHUN 2011-2015 - B1013131047, Daniel Gultom (Jurnal Pembangunan dan Pemerataan, 2018)
One of the strengths supporting the implementation of development in the region is the availability of capital expenditure budget. Acquisition of fixed assets will increase the capital stock. Supported by the readiness of facilities and infrastructure of public goods economic activities will be smooth. Economic growth and people's welfare are the goals of local governments to achieve in accordance with the mandate of regional autonomy and the implementation of decentralization. The local government in financing the capital expenditure is financed from the Regional Budget (APBD) based on the legislation. This study aims to examine the influence of factors of Local Original Revenue (PAD) and General Allocation Fund (DAU) to the dependent variable of capital expenditure.Â Keywords: Pendapatan Asli Daerah (PAD), General Allocation Fund (DAU), Capital Expenditure.